Hierarchical structured graphene/metal oxide/porous carbon composites as anode materials for lithium-ion batteries - Guo, Rong; Yue, Wenbo; Ren, Yu; Zhou, Wuzong (Materials research bulletin, 2016)
[Display omitted] •CeO2 and Co3O4 nanoparticles display different behavior within CMK-3.•CMK-3-CeO2 and Co3O4 show various electrochemical properties•CMK-3-CeO2 and Co3O4 are further wrapped by graphene nanosheets.•Graphene-encapsulated composites show better electrochemical performances. As a novel anode material for lithium-ion batteries, CeO2 displays imperceptible volumetric and morphological changes during the lithium insertion and extraction processes, and thereby exhibits good cycling stability. However, the low theoretical capacity and poor electronic conductivity of CeO2 hinder its practical application. In contrast, Co3O4 possesses high theoretical capacity, but undergoes huge volume change during cycling. To overcome these issues, CeO2 and Co3O4 nanoparticles are formed inside the pores of CMK-3 and display various electrochemical behaviors due to the different morphological structures of CeO2 and Co3O4 within CMK-3. Moreover, the graphene/metal oxide/CMK-3 composites with a hierarchical structure are then prepared and exhibit better electrochemical performances than metal oxides with or without CMK-3. This novel synthesis strategy is hopefully employed in the electrode materials design for Li-ion batteries or other energy conversion and storage devices.